What can happiness research tell us about altruism? Evidence from the German Socio-Economic Panel - Johannes Schwarze; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2005)
Much progress has been made in recent years on developing and applying a direct measure of utility using survey questions on subjective well-being. In this paper we explore whether this new type of measurement can be fruitfully applied to the study of interdependent utility in general, and altruism between parents and adult children who moved away from home in particular. We introduce an appropriate econometric methodology and, using data from the German Socio-Economic Panel for the years 2000-2004, find that the parents' self-reported happiness depends positively on the happiness of their adult children. A one standard deviation move in the child's happiness has the same effect as a 45 percent move in household income.
Keywords: D6; D64; C25; J10; 330; Utility function; Extended family; Fixed effects; Ordered probit; Altruismus; Familie; Lebensqualität; Schätzung; Deutschland; Eltern